El Excentrico, 1956-11-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
November 20, 1956 [20 de noviembre de 1956]. Ano 7, No 6. Cover contains a photo of model, Agnus Martinez with headline, "Miss Agnus Martinez all dolled up to celebrate Thanksgiving."